A study of CMMS failure - Lee, Cheng Hui; Khor, Jiunn Keang; Mohd Yusof, Fattiyah; Mohd Nawi, Mohd Nasrun (2013)
Maintenance work has become more important to the organization nowadays.This study is a comprehensive review of the reliability of implementation Computerise Maintenance Management System (CMMS) in construction industry. The focus of the discussion is more related to the cause of failure of CMMS.It based on the disclosed some cases for further understand that particularly about the problem which is including the cause and solution for the future improvement of the problem.In the end of this study, some recommendations have been provided to prevent the failure.